Impact of the COVID-19 pandemic on the consumption of antibiotics and the emergence of AMR: case study in a general hospital - Rozman, Urška; Kranjec, Konrad; Šeruga, Aleksander; Kramar, Urška; Vrbnjak, Dominika; Lavrič, Miha; Turk, Sonja Šostar (Frontiers in Public Health, 2025)
ObjectivesThe COVID-19 pandemic changed the use of antibiotics and had an impact on the development of antimicrobial resistance. The study aimed to examine the consumption of antibiotics and the occurrence of AMR infection and colonization in the selected general hospital.MethodsData on antibiotic consumption and data on AMR infections and colonization were monitored in the period before the COVID-19 pandemic (2018, 2019) and during the COVID-19 pandemic (2020, 2021). Descriptive statistics, the Mann–Whitney U test, and the Pearson or Spearman correlation test were used.ResultsThe overall prescription of antibiotics stayed approximately the same, however, some important differences can be observed when analyzing specific groups of antibiotics (vancomycin, linezolid, piperacillin/tazobactam, meropenem, colistin). We did not observe the difference in the occurrence of AMR infections and colonizations before and during the pandemic. However, we did observe an alarming increase in CRaB, ESBL and VRE and highlighted the increase in all AMR groups between the first and second year of the pandemic.ConclusionThe connection between antibiotic consumption and the occurrence of AMR infections and colonization was confirmed.